Aplicação foliar de indutor de resistência em feijoeiro comum: efeito sobre desempenho da cultura, qualidade fisiológica e sanitária das sementes - Neves, Graciele [UNESP] (2014)
Fertilizers has the purpose of nutrition, stimulate development and protection of plants against microorganisms, by foliar applications, soil applications or by seed applications. Thus, the present study was developed aiming to verify the effect of the application of the product containing salicylic acid and nitrogen (10%) foliar applications in both cultivars and in three phenological stages. The experiment was performed on Education Farm Research and Extension UNESP, located in Selvíria, MS, in 2012 and 2013. The treatments were arranged in a randomized complete blocks, factorial (5x3x2) with four replications, composed of five rates of leaf product (0 , 1.0, 1.5, 2.0 and 2.5 L ha-1) with formulation of salicylic acid with 10% nitrogen in three stages (V4-3, V4-6 e R5) of both cultivars beans (IAC-Alvorada e Verde-ISA). Considering the sanitary aspect of culture were assessed, fresh weight, number of grenades and empty pods per plant, total chlorophyll content, leaf N content, grain yield, germination, electric conductivity, accelerated aging, controlled deterioration and sanitary quality of seeds. The IAC-Alvorada and Green-ISA cultivars had similar productivity. The leaf product containing inducer of resistance did not affect yield of the cultivars IAC-Alvorada and Green-ISA. In case of application of the product, when performed during the vegetative stages (V4-3 and V4-6) was more efficient for the application in R5. Germination did not differ between cultivars, however, to analyze the effect cv. IAC Dawn presented better features. Due to the low incidence of pathogens in seeds from harvests of 2012 and 2013 cultivars, it is not possible to verify the capability of the leaf containing product inducer of resistance. Fertilizers is intended to nourish, stimulate development and protect the plant against microorganisms, for foliar applications, the soil or via seed, and we can be great addition to the main fertilizer. Thus, the present ...